2018
DOI: 10.1111/cdev.13026
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Following Is Not Dependent on Ostensive Cues: A Critical Test of Natural Pedagogy

Abstract: The theory of natural pedagogy stipulates that infants follow gaze because they are sensitive to the communicative intent of others. According to this theory, gaze following should be present if, and only if, accompanied by at least one of a set of specific ostensive cues. The current article demonstrates gaze following in a range of contexts, both with and without expressions of communicative intent in a between-subjects design with a large sample of 6-month-old infants (n = 94). Thus, conceptually replicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 39 publications
8
86
1
Order By: Relevance
“…First, Ni-Vanuatu infants followed the gaze of a person on the computer screen and did so at the age comparable to the youngest Western infants tested using similar procedures (Gredebäck et al, 2008(Gredebäck et al, , 2018Senju & Csibra, 2008;Szufnarowska et al, 2014 Even though Ni-Vanuatu 5-to 7-month-olds in our study spent more time looking at the gazed-at target rather than the distractor (in IDS condition), they did not tend to saccade to the target first. First, Ni-Vanuatu infants followed the gaze of a person on the computer screen and did so at the age comparable to the youngest Western infants tested using similar procedures (Gredebäck et al, 2008(Gredebäck et al, , 2018Senju & Csibra, 2008;Szufnarowska et al, 2014 Even though Ni-Vanuatu 5-to 7-month-olds in our study spent more time looking at the gazed-at target rather than the distractor (in IDS condition), they did not tend to saccade to the target first.…”
Section: Similarities In the Patterns Of Performance Of Melanesian Andmentioning
confidence: 63%
See 3 more Smart Citations
“…First, Ni-Vanuatu infants followed the gaze of a person on the computer screen and did so at the age comparable to the youngest Western infants tested using similar procedures (Gredebäck et al, 2008(Gredebäck et al, , 2018Senju & Csibra, 2008;Szufnarowska et al, 2014 Even though Ni-Vanuatu 5-to 7-month-olds in our study spent more time looking at the gazed-at target rather than the distractor (in IDS condition), they did not tend to saccade to the target first. First, Ni-Vanuatu infants followed the gaze of a person on the computer screen and did so at the age comparable to the youngest Western infants tested using similar procedures (Gredebäck et al, 2008(Gredebäck et al, , 2018Senju & Csibra, 2008;Szufnarowska et al, 2014 Even though Ni-Vanuatu 5-to 7-month-olds in our study spent more time looking at the gazed-at target rather than the distractor (in IDS condition), they did not tend to saccade to the target first.…”
Section: Similarities In the Patterns Of Performance Of Melanesian Andmentioning
confidence: 63%
“…We used an eye-tracking paradigm (Gredebäck et al, 2008(Gredebäck et al, , 2018Senju & Csibra, 2008;Szufnarowska et al, 2014) to assess gaze-following responses of 5-to 7-months-old infants in the same rural Melanesian small-scale society of Tanna island, in the same general region where Little et al (2016) found face-to-face contact in triadic interactions to be less prevalent than in Western population. We used an eye-tracking paradigm (Gredebäck et al, 2008(Gredebäck et al, , 2018Senju & Csibra, 2008;Szufnarowska et al, 2014) to assess gaze-following responses of 5-to 7-months-old infants in the same rural Melanesian small-scale society of Tanna island, in the same general region where Little et al (2016) found face-to-face contact in triadic interactions to be less prevalent than in Western population.…”
Section: Research Highlightsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cornerstones of the perceptual narrowing idea are (1) that infants are born with a form of attentional bias that enables a preference for speech sounds and faces that is rather broad (i.e., extended to monkey calls and inverted face‐like displays); and (2) that the initial sensitiveness progressively refines through individualized experiences (e.g., hearing a particular voice and seeing the faces of a specific group of people, and eventually showing a preference/being more skilled at discriminating familiar items than unfamiliar ones). Correspondingly, newborns and young infants show an attentive bias to the direction of gaze expressed as shifts in head and eye‐gaze direction (Farroni, Johnson, & Csibra, ): this initial sensitivity is rather broad for the first months, as a broad range of stimuli and agents implement early GF based on low‐level cues, as highlighted by numerous authors (Deák, ; Farroni, Massaccesi et al., 2004; Gredebäck et al., ; Meltzoff & Brooks, ; Moore et al., ). Progressively, the close interaction with the environment fine tunes neural networks dedicated to GF that might undergo a perceptual narrowing similar to what has been demonstrated for face perception and language (Maurer & Werker, ): Infants become attuned to specific directional cues that they are mostly exposed to and start to ignore non‐specific but salient cues (e.g., eye‐gaze shift versus head motion).…”
Section: Theoretical Perspectives On the Developmental Origins Of Gfmentioning
confidence: 99%